Распределение радона на территории города Кемерово - Верховых Ю.А.; Строкова Людмила Александровна (My University, 2016)
A primary radon potential mapping based on field soil gas radon and soil descriptions was carried in this study. The results reveal that Quaternary sediments are inhomogeneous from a radon point of view. The analysis of certain geological information can allow classifying with high probability certain areas as radon'prone. This information is very useful for planning justified radon prevention in new buildings.
The distribution of radon on the territory of the city of Kemerovo
Keywords: Кемерово; радиоэкологические ситуации; радон; геологическое строение; радиометры